2017
DOI: 10.1021/acs.organomet.7b00411
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decarbonylation of Fatty Acid Esters to Linear α-Olefins

Abstract: Selective decarbonylation of p-nitrophenol esters of fatty acids to the corresponding linear α-olefins (LAOs) was achieved using palladium catalysis. After extensive ligand screening, a mixed-ligand system exploiting the trans-spanning diphosphine XantPhos and an N-heterocyclic carbene (IPr) was identified as the most effective in yielding high α-selectivity and high conversions of the ester (>98% selectivity, >90% conversion using 2.5 mol % of PdCl2 and 5 mol % of the ligands, 190 °C, 2–2.5 h). On the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 71 publications
1
52
0
Order By: Relevance
“…Previous DFT studies in homogeneous Pd catalysts 30,44 suggested dehydrogenations as rate-determining TSs, while the present work on Pd(111) surfaces points toward the C−C bond breaking process (TS-C3). Interestingly, the relative activation energies for dehydrogenation (from the prior alkyl intermediate to the corresponding TS) are quite similar for…”
Section: Research Articlementioning
confidence: 49%
See 1 more Smart Citation
“…Previous DFT studies in homogeneous Pd catalysts 30,44 suggested dehydrogenations as rate-determining TSs, while the present work on Pd(111) surfaces points toward the C−C bond breaking process (TS-C3). Interestingly, the relative activation energies for dehydrogenation (from the prior alkyl intermediate to the corresponding TS) are quite similar for…”
Section: Research Articlementioning
confidence: 49%
“…82 Indeed, the hemilabile behavior of these ligands have been reported in homogeneous systems. 30,83 In the gas phase, the relaxed conformation of the phosphine coming from C1 is only 0.20 eV less stable than that coming from C. It is clear than the energy toll essentially emerges from the loss of Pd•••P and Pd•••C interactions after partial decoordination. Additionally, starting from the DPEPhos Me model, we included two Ph groups in the P atom that detaches from the surface to better mimic the complete DPEPhos ligand.…”
Section: Acs Catalysismentioning
confidence: 99%
“…We started our investigations with the biaryl acid fluoride 1 a , utilizing Xantphos as the ligand for Pd. Although Xantphos has never been effective in catalytic trifluoromethylations, it is one of the few ligands capable of facilitating reductive elimination from [L n Pd II (Ar)(CF 3 )] ,. To our delight 15 % of the desired product ArCF 3 2 a (see Table ) was formed in our initial investigations employing TMSCF 3 as transmetalating agent.…”
Section: Figurementioning
confidence: 96%
“…The highest activities and selectivities have so far been obtained with homogenous catalysts [2,14,22]. Homogeneously catalyzed decarbonylative dehydration has proven to be a promising reaction in the production of LAOs [12][13][14][15][22][23][24][25][26][27][28][29][30], as well as in the toolbox of the synthetic organic chemist [31].…”
Section: Introductionmentioning
confidence: 99%
“…With this promising outlook, transition-metal catalysts based on palladium [12][13][14][15]22,25,29,30,32], rhodium [14,23], iridium [27,33], nickel, [24,34], and iron [28] have been developed. Palladium-based catalysts have so far reached the highest activities [14].…”
Section: Introductionmentioning
confidence: 99%